Legal Certainty for Children Born Through Surrogacy in Indonesia: A Normative Juridical Analysis - I Gede Taruna Santosa; I Nyoman Bagiastra (International Journal of Business, Law, and Education, 2026)
Surrogacy presents a regulatory paradox in Indonesia. The current health-law framework permits assisted reproduction only for legally married spouses using their own gametes and requires embryo transfer to the wife from whom the ovum originates. It therefore excludes gestational surrogacy from authorized medical practice. Nevertheless, the same framework does not comprehensively determine the parentage, civil status, registration, and protection of a child who is born through a clandestine domestic arrangement or a cross-border surrogacy arrangement. This study examines that gap through normative juridical research using statutory and conceptual approaches. The analysis covers constitutional child-rights guarantees, marriage and civil law, health legislation, regulations on assisted reproduction, adoption rules, and Constitutional Court Decision No. 46/PUU-VIII/2010. The study finds that a surrogacy agreement is unlikely to be enforceable because its purpose conflicts with mandatory health-law provisions and the lawful-cause requirement of Indonesian contract law. However, the invalidity of the adults' arrangement cannot extinguish the child's independent constitutional rights. Scientific evidence may support a civil relationship with the genetic father under the Constitutional Court's reasoning, but Indonesian positive law still provides no equally clear route for recognizing the genetic intended mother. Adoption can provide interim protection, yet it changes the juridical basis of the relationship and cannot substitute for a specific parentage regime. A progressive-law approach therefore requires a child-centred framework that separates the regulation of adult conduct from the protection of children, guarantees birth registration and identity, enables judicial determination of parentage, allocates parental responsibilities, preserves the right to origins, and addresses cross-border cases.